KUALITAS HUBUNGAN SEBAGAI MEDIASI PENGARUH KUALITAS PRODUK DAN NILAI TERHADAP LOYALITAS (Studi pada Komsumen Mobil Hyundai dan KIA di Jawa Timur) - Arwani, Mokhamad (Jurnal Analisis Manajemen, 2011)
This study aims to describe and explain the product quality, product value, and quality of relationships in shaping consumer loyalty. On the operational development of theoretical models of this study can be done through express and interpret the relationship between product quality and product value on loyalty. Testing the mediating role of relationship quality in relation to the influence of product quality and product value on loyalty. Sampling was carried out by proportional stratified random sampling method. In this research study is a partial sample of consumers Korean cars in Indonesia. Amount of sample that meets the requirements of 114. This amount is in accordance with the calculation that says that the sample size depends on the number of indicators used in all the variables multiplied by 5 to 10. The results showed that increasing product quality and value of the product increases the quality of relationships between companies and customers and further increase customer loyalty. The stronger the mediating role of relationship quality the more it will enhance the relationship between product quality and product value on customer loyalty.